Autoimmune pancreatitis as a very rare cause of recurrent pancreatitis in children; a case report and review of literature - Shashaani, Niloufar; Hosseini, Amirhossein; Imanzadeh, Negar; Dara, Naghi; Matani, Rahman; Sayyari, Aliakbar (Student Research in Translational Medicine, 2020)
Autoimmune pancreatitis as chronic inflammation of the pancreas due to an autoimmune mechanism is a rare type of pancreatitis. A 14 years old girl presented with multiple episodes of abdominal pain, nausea with elevation of amylase and lipase suspicions of acute recurrent pancreatitis since 3 years of age. After through evaluation about secondary causes of recurrent and familial pancreatitis finally she responded to corticosteroid treatment. Although very rare but autoimmune processes should be considered in teenagers with recurrent pancreatitis.